2000
DOI: 10.1046/j.1440-1746.2000.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a 1‐week pantoprazole triple therapy in eradicating Helicobacter pylori in Asian patients

Abstract: The pantoprazole 1-week triple therapy with amoxycillin and clarithromycin is effective in H. pylori eradication. The treatment was well tolerated by patients. Metronidazole resistance was reported in a high percentage of strains isolated from patients. Clarithromycin resistance was, however, not detected in any of the strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 14 publications
3
28
1
2
Order By: Relevance
“…In the Malaysian setting we have been monitoring H. pylori resistance to antibiotics periodically and our data showed that clarithromycin resistance rates have remained consistently low or absent over the years 5,30–32 . In another report from Malaysia, a similarly low clarithromycin resistance rate was reported 33 .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In the Malaysian setting we have been monitoring H. pylori resistance to antibiotics periodically and our data showed that clarithromycin resistance rates have remained consistently low or absent over the years 5,30–32 . In another report from Malaysia, a similarly low clarithromycin resistance rate was reported 33 .…”
Section: Discussionmentioning
confidence: 56%
“…In another report from Malaysia, a similarly low clarithromycin resistance rate was reported 33 . Metronidazole resistance has been noted to be too high (over 70%) to be of any value in clinical use for H. pylori eradication in our setting 5,31 . Amoxycillin resistance is zero in the latest study from our center and remains a useful drug in the treatment of H. pylori 31…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The combination of PPI with amoxicillin and metronidazole, on the other hand, has consistently given lower eradication rates 4–6 . This is inherently a less potent treatment regimen and is further weighed down by the high resistance to metronidazole in many parts of the world, especially in Asia 8–10 . Both metronidazole and clarithromycin resistance have been shown to impact adversely on treatment success and are reported to cause a drop in eradication rates of over 50% 11 …”
Section: Introductionmentioning
confidence: 99%
“…Those tested positive were given eradication treatment consisting of pantoprazole 40 mg, amoxycillin 1 g and clarithromycin 500 mg twice a day each, for 1 week. This regime had previously been found to have an eradication success rate of 90.7% locally 18. Adults who were allergic to penicillin were given metronidazole instead.…”
Section: Methodsmentioning
confidence: 99%